Effects of different plant growth regulators on in vitro growth of Aloe vera L. (Bangladesh Journal of Botany, 2020)
An attempt was made to standardize the appropriate concentration of different growth regulators for successful in vitro growth of different explants (leaf, node and internode) of Aloe vera L. Results demonstrated best in vitro growth in leaf explants in MS medium supplemented with BAP (1.0 mg/l) and NAA (1.0 mg/l) at 26 ± 2ºC) with pH 5.70 using agar solidified medium and 16 hrs photoperiod.